Math Bilbul: Development of Construct 2-Based Gamification Learning Media on Integer Number Material for VII Grade - Maysitta Dyah Afsara; Sari Saraswati (Jurnal Inovasi Matematika, 2025)
This study aims to produce a valid, practical, and effective Math Bilbul gamification learning media based on Construct 2 on integer number material in VII grade. The development model used is 4D (Define, Design, Develop, Disseminate). Data collection techniques use observation, documentation, tests, and questionnaires. The instruments used are validation sheets, 8 descriptive questions and user response questionnaires. Data are analyzed descriptively quantitatively according to the research stage. The results of qualitative validation by material experts reached a score percentage of 94.7% and media of 92% with very valid criteria. The results of student and teacher responses at the small and large class trial stages showed that the media developed was very practical and effective to use based on the results of classical learning completion of 90%. This Math-bilbul can be used as an alternative interactive game-based learning media.